The tragedy of the uncommons: Reframing workforce diversity. (February 2013) - Jonsen, Karsten; Tatli, Ahu; Özbilgin, Mustafa F; Bell, Myrtle P
This article presents a reframing of workforce diversity as a social tragedy. We draw on Hardin's concept of 'tragedy of the commons', which explored the conflicts between individual and collective good. We identify two dilemmas that underscore the social tragedy of diversity and explain why they prevent workforce diversity from progressing: (1) voluntarism and (2) individualism. We critique the simplistic models of managing diversity and suggest an alternative conceptualization as a way forward. We advocate an approach that captures the potential contradictions between individual and social good and accounts for the role of multiple actors in tackling the tragedy of the uncommons. A reframing of organizational self-interest and collective interests in the context of diversity is presented and solutions to social tragedy of diversity are proposed.